A case of primary biliary cirrhosis with high titers of antinunclear antibody and distual ulserative colitis in remission - Senem KÜÇÜKBAŞ; Cemil EKİNCİ; Nurgül ŞAŞMAZ (Turkish Journal of Gastroenterology, 2019)
-